Legal protection on endangered species: Malayan tapir and tiger / Hartini Hawari ... [et al.] - Hawari, Hartini; Mohamed Idris, Iliqa Minhalina; L.M.N. Azhar, Sharifah Nurina Permatasari; Omar, Siti Saidah Nafisah (2009)
The purpose of this project paper is to discuss on the law and protection provided for endangered species in Malaysia specifically focuses on Malayan Tiger and Malayan Tapir. This research is made due to alarming issues on these animals which have been threatened. This animal also has been listed as the endangered species protected under the Protection of Wildlife Act 1972. Malayan tiger and tapir encounter a serious problem which in danger of extinction and lost of it habitats from its original. The extinction of these two animals is because of rapid deforestation and development and also illegal poaching by human being which become more serious year to year. Though there are several laws and policies have been implemented in protecting and sustaining the population of these two animals, however the existing laws are still insufficient to curb with the extinction of the Malayan Tiger and Tapir. This research aims to examine whether step taken by the government, non-governmental organizations and international bodies are sufficient in protecting these two animals which are the Malayan Tiger and Tapir. These steps are important to safeguard this animal from extinction and to preserve and maintain for present and future generation. Next, this research paper aims in providing the appropriate law and regulations in imposing an accurate punishments and penalties in order to safeguard the population of the Malayan Tiger and Malayan Tapir. This is necessary for the purpose to prevent the offender from committing any crime such as illegal trade, poaching and deforestation.